2017
DOI: 10.4103/ijccm.ijccm_159_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Candida scoring systems to predict early candidemia: A prospective and observational study at a tertiary care hospital, Uttarakhand

Abstract: Background:Candidemia in critically ill patients is usually a severe and life-threatening condition. Furthermore, due to its nonspecific presentation, it is difficult to diagnose leading to delayed treatment, prolonged hospitalization, and increased health-care costs with increase in morbidity and mortality.Objectives:In view of lack of data on “Candida scoring systems,” this study was designed to evaluate the effectiveness of these scoring systems in predicting the development of candidemia among the Intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…In the present study the higher prevalence of Candida species was seen in males, which coincides well with the Gupta et al 5 where as much higher prevalence shown by Xess et al 6 and lower prevalence shown by Singh and Abraham. 7 It is concluded that males are more prone to Candida infection because of poor hygiene, diabetes and prolonged use of antibiotics and the yeast like fungus form normal commensal of oral, mucosal, gastrointestinal and genitourinary tract of human.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study the higher prevalence of Candida species was seen in males, which coincides well with the Gupta et al 5 where as much higher prevalence shown by Xess et al 6 and lower prevalence shown by Singh and Abraham. 7 It is concluded that males are more prone to Candida infection because of poor hygiene, diabetes and prolonged use of antibiotics and the yeast like fungus form normal commensal of oral, mucosal, gastrointestinal and genitourinary tract of human.…”
Section: Discussionsupporting
confidence: 92%
“…Dharvad and Dominic (2011) showed higher prevalence by C. albicans (47%) followed by C. tropicalis (30%), C.krusei (14%) and C. glabrata (9%). 8,13 Deorukhkar and Saini (2012) and Gupta et al (2015) showed higher prevalence by C. albicans. 5 Chander et al (2013) and Kaur et al (2014) showed higher prevalence by C. tropicalis.…”
Section: Discussionmentioning
confidence: 92%
“…In that study, it was concluded that Leone score of ≥2.5 is most suitable for ruling in the diagnosis of invasive candidiasis. 12 However, Leon et al and Blumberg et al reported Total Parenteral Nutrition (TPN) as a clinically significant risk factor; similarly, we observed only 03 patients on TPN and out of them 02 were having candidemia. But the relation cannot be established due to lower usage of TPN in our ICU during the study period.…”
Section: Discussionsupporting
confidence: 60%
“…C. albicans and C. parapsilosis were the most prevalent species isolated from blood samples. C. albicans has been repeatedly identified in studies as the most common yeast species [ 7 , 9 , 21 , 22 ]. C. parapsilosis was the second Candida species in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although in this study, 77.3% of patients had received at least one antifungal drug, the mortality rate was high (63.6%). However, higher mortality rates have also been reported [ 21 ]. Our findings suggest that patients with C. albicans candidemia have the lowest mortality rate (41.7%).…”
Section: Discussionmentioning
confidence: 99%